2011
DOI: 10.1007/s10974-011-9240-2
|View full text |Cite
|
Sign up to set email alerts
|

A force-activated kinase in a catch smooth muscle

Abstract: Permeabilized anterior byssus retractor muscles (ABRM) from Mytilus edulis were used as a simple system to test whether there is a stretch dependent activation of a kinase as has been postulated for titin and the mini-titin twitchin. The ABRM is a smooth muscle that shows catch, a condition of high force maintenance and resistance to stretch following stimulation when the intracellular Ca++ concentration has diminished to sub-maximum levels. In the catch state twitchin is unphosphorylated, and the muscle maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Calmodulin has been shown to bind the CRD of TK and TwcK in vitro (10), but it does not lead to significant activation (9,11). Recently, in agreement with the involvement of these kinases in stretch-mediated pathways, it has been suggested that the tension that builds up in the cytoskeleton during muscle function pulls the CRD from the kinase, causing its release by mechanical unfolding (3,4). The stretch-activation of human TK studied by atomic force microscopy (AFM) and molecular dynamics (MD) simulations (12)(13)(14)(15) indicated that strain might lead to an ordered sequence of conformational changes that unwind the CRD, leaving an active kinase core.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Calmodulin has been shown to bind the CRD of TK and TwcK in vitro (10), but it does not lead to significant activation (9,11). Recently, in agreement with the involvement of these kinases in stretch-mediated pathways, it has been suggested that the tension that builds up in the cytoskeleton during muscle function pulls the CRD from the kinase, causing its release by mechanical unfolding (3,4). The stretch-activation of human TK studied by atomic force microscopy (AFM) and molecular dynamics (MD) simulations (12)(13)(14)(15) indicated that strain might lead to an ordered sequence of conformational changes that unwind the CRD, leaving an active kinase core.…”
mentioning
confidence: 76%
“…Further, the conserved Ig-Ig-Fn tandem preceding TK is a receptor site for the ubiquitin ligase MuRF1 (5, 6), which is linked to the atrophy that results from muscle disuse. In TwcK, mechanical stress has been correlated with increased kinase activity (4). These data suggest that titin-like kinases form mechanosensory signaling nodes central to myofibril regulation.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The phosphorylation of myorod at the two different sites of the molecule indicates the possibility of regulation of its unknown function. For example, twitchin is seems to be a force-sensitive kinase, which is thought to be activated by stretch that results in its autophosphorylation [ 26 ]. The idea that twitchin is a mechanical link interconnecting thin and thick filaments [ 12 ] though its interaction with actin [ 18 ] and myosin [ 12 ; 27 ] or myorod and paramyosin [ 12 ] supports this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that the 5-HT-induced relaxation of the catch state is mediated by cyclic AMP(cAMP), which activates protein kinase A to result in the phosphorylation of a high molecular mass (~600 kDa) protein, twitchin [ 20 , 41 , 42 ]. Butler et al [ 43 ] recently reported that, in skinned ABRM fibers, twitchin phosphorylation increases in stretched fibers, suggesting that twitchin senses tension in the ABRM, to result in an increase in twitchin kinase activation. However, this phenomenon is related to the relaxation of the catch state, but not to the establishment of the catch state.…”
Section: Possible Mechanism Of the Catch State Coupled With Intracmentioning
confidence: 99%